SURVEYING STUDENTS’ LEARNING PREFERENCES: MEMORIZING VS UNDERSTANDING CHEMISTRY ENGLISH TERMS - Rahma, Keysha; Syava, Nazwa; Wahyunengsih, Wahyunengsih (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2025)
English words appear everywhere in chemistry classes. They appear in lecture slides, practical notes, lab reports, and the articles students read for assignments. Even so, knowing the words on paper does not mean students feel comfortable using them. Quite a few say they can memorize terms for an exam, but the meaning slips away when they need to explain or apply the terms in actual writing. This led the researcher to examine how chemistry students actually study these terms, whether they mostly memorize definitions or try to understand their meanings and how they are used. Fifty chemistry students took part in an online questionnaire with a five-point Likert response scale. The answers were summarized descriptively to see which learning pattern stood out most. The results show that memorization remains prevalent, especially during exam periods. The highest mean score was 3.76 for “I often memorize chemistry terms without understanding their use.” Understanding concepts, however, seemed more helpful for remembering long-term, with a mean of 3.63. Even more substantial was the impact of repeated exposure to terminology during academic tasks, which reached 3.91. From these numbers, memorization helps for a short time, but the effect fades if the terms are not used again. When students understand a term and later encounter it repeatedly in class activities, the vocabulary tends to stick and feel easier to use naturally, rather than just for passing tests. These findings may contribute to the Development of learning strategies that encourage continuous vocabulary practice, allowing terms to be applied not only in exams, but also in honest academic communication.